Development of Educational Instruments for Postpartum Care with Severe Preeclampsia-Eclampsia based on the Health Promotion Model (HPM) - Endah Suprihatin; Sri Hardi Wuryaningsih (Humanistic Network for Science and Technology (HNST), 2022)
An educational instrument is needed that is in accordance with the needs of postpartum mothers with severe preeclampsia-eclampsia. The nursing theories that views the importance of health promotion as an effort to prevent complications has been produced by Nola. J Pender as a Health Promotion Model (HPM). This study aims to develop an educational instrument for postpartum mothers with severe preeclampsia-eclampsia based on the HPM. The design of this research was research and development (R & D) which consisted of 2 stages, namely the development stage and the trial stage. The samples in this study were 50 midwives, 10 postpartum mothers, and an educational media that had been used by midwives. Data were collected through interviews, filling out questionnaires and FGD. A specific educational instrument has been developed by adding components to understanding the benefits of action, understanding prevention efforts, understanding the effectiveness of actions, and the effect on activities. Educational instruments based on the HPM get good results after being socialized and tested, and have met the aspects of functionality, efficiency, and usability, so that they can be used as an instrument to educate post partum patients with severe preeclampsia and eclampsia in the work area of the Health Office of Surabaya.Keywords: post partum; severe preeclampsia-eclampsia; educational instruments; health promotion model